Gene age shapes functional and evolutionary properties of the Drosophila seminal fluid proteome - Jose M. Ranz; Carolina Flacchi; Imtiyaz E. Hariyani; Alberto Civetta (Proceedings of the National Academy of Sciences, 2025)
Seminal fluid proteins (Sfps) are crucial for animal reproductive success, with Sfp-encoding genes believed to be evolutionarily young due to heightened rates of gene loss and gain and rapidly evolving at the sequence level relative to other genes. Using estimates of the phylogenetic origin of each Drosophila melanogaster Sfp gene, based on genomic resources that include outgroup species to the Drosophila genus, we examined the functional attributes and evolutionary characteristics of 357 Sfp genes relative to their evolutionary age. Contrary to the perception that many Sfp genes are evolutionarily young, 62% existed in the genome of the ancestor to this genus. These ancient genes have broader expression profiles, more expansive biological roles, and have more interactions with non-Sfp genes. This increased pleiotropy has imposed constraints on the rate of sequence evolution in ancient Sfp genes compared to younger ones. Notably, these younger Sfp genes evolve substantially faster as a result of both adaptive and nonadaptive evolutionary forces. Within the Sfp interactome, we identified a fast-evolving core subnetwork of younger genes with more restricted tissue expression and functions. Our systematic approach has uncovered a large set of ancient Sfp genes with distinct genomic, functional, and evolutionary characteristics compared to the younger, more commonly studied Sfp genes. With increased refined genomic and functional data acquisition across a wider variety of taxa, our approach and results serve as proof of the importance of systemic strategies applied to broadly defined gene sets based on their time of evolutionary origination.